Pale by comparison: competitive interactions between signaling female glow-worms. (4th December 2018) - Borshagovski, Anna-Maria; Baudry, Gautier; Hopkins, Juhani; Kaitala, Arja
Abstract : When individuals differ in attractiveness, less attractive ones may fail to mate. In the common glow-worm, females glow to attract flying males, which prefer brighter females. We show that females move away from more attractive competitors, possibly to avoid comparison. In nature, females glowed far from each other. As distance between females may affect how males perceive female attractiveness, dim females may appear bright if close by and if comparison is not possible for males. Abstract: When individuals differ in their abilities to compete for a mate, weaker competitors may evolve tactics to increase their mating success. Exploiting attractiveness of others to get mates is a common tactic in many taxa, although examples of this behavior in females are scarce. In glow-worms ( Lampyris noctiluca L., Coleoptera: Lampyridae), females attract males by glowing and males prefer the brightest female. How unattractive females succeed in competition for mates is largely understudied. We hypothesize that less attractive female glow-worms may succeed in competition over mates by parasitizing glow of more attractive competitors. We tested our hypothesis with a combination of field and laboratory experiments. Contrary to our expectations, we found that females move away from brighter competitors. This behavior may explain our field observation that females are often more than 1 m apart from each other. Increasing distance to a brighter female may make comparison on brightness difficult for males and increase attractiveness of dimmer females. Our study provides evidence of behavior by which less attractive competitors may actively avoid competition and therefore affect female distribution in nature. This behavior may explain maintenance of variation in attractiveness of sexual signals, even in species where mates are selected by ornaments. We conclude that sexual competition may play a crucial role in spatial distribution. Spatial distribution of competing sex affects choosing individuals' ability to compare mates and thus affects mate choice.